2020
DOI: 10.21815/jde.019.167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blended Learning on Dental Students' Performance and Satisfaction in Clinical Education

Abstract: The aim of this study was to evaluate the effectiveness of a blended learning model with a flipped classroom approach in a clinical dental education setting based on student performance and perceptions. Comparisons were made between blended learning and traditional methods for all fourth-year dental students in two consecutive cohorts in a conservative dentistry course at a dental school in Jordan. The 2016-17 cohort (control group) consisted of 364 students taught with conventional methods. The 2017-18 cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 35 publications
6
53
0
6
Order By: Relevance
“…Qutieshat et al [ 34 ] compared the effectiveness of blended learning and traditional methods for fourth-year dental students in two consecutive cohorts in a conservative dentistry course. Blended-learning students achieved significantly higher grades than traditionally taught students.…”
Section: Discussionmentioning
confidence: 99%
“…Qutieshat et al [ 34 ] compared the effectiveness of blended learning and traditional methods for fourth-year dental students in two consecutive cohorts in a conservative dentistry course. Blended-learning students achieved significantly higher grades than traditionally taught students.…”
Section: Discussionmentioning
confidence: 99%
“…Thematic analysis Not indicated [ 125 ] Nursing students (1st year) To teach a first-year course on health assessment Flipped classroom Canada Effectiveness; satisfaction; efficiency No Student grades; feedback (comparison between different cohort of students—intervention vs. no intervention) Not indicated [ 81 ] Pharmacy students (1st, 2nd, and 3rd year) To teach three courses: (1) small ambulatory care; (2) cardiovascular pharmacotherapeutics; and (3) evidence-based medicine Blended learning USA Effectiveness; satisfaction; efficiency No Exam grades; student survey; and additional open-ended questions asked to faculty. Thematic analysis on open ended questions Not indicated [ 68 ] Medical students; dental students; pharmacy students To teach physiology Blended learning Montenegro Effectiveness; satisfaction; efficiency No Comparison of grades on assessments between intervention and non-intervention group; survey (Likert scale 1–5); use of online material Not indicated [ 126 ] Dental students (4th year) To teach conservative dentistry and clinical dental skills in a course Blended learning with a flipped classroom approach Jordan Effectiveness; satisfaction No Comparison between students being taught via blended learning and traditional methods; performance measures included two exams, two assignments, in-clinic quizzes, and a clinical assessment; number of posts made by students in study groups and online discussion forums; and a questionnaire Not indicated [ 127 ] Emergency medicine residents (post graduate year 3) To teach a cour...…”
Section: Resultsmentioning
confidence: 99%
“…Group (A) (Ahmed, 2011;Al-Hasan, 2013;Almasaeid, 2014;Chen and Jones, 2007;Dowling, Godfrey and Gyles, 2003;Khader, 2016;Kagohara, et al, 2010;Lança and Bjerre, 2018;McLaughlin, et al, 2015;Qutieshat, Abusamak and Maragha, 2019).…”
Section: Previous Studies Of Group Aim Of Studies Main Resultsmentioning
confidence: 99%
“…In educational institutions such as universities, blended learning and its impact on student achievement has been studied extensively. Several blended learning studies revealed that the blended learning methodology has beneficial effects on student performance, engagement, and involvement in the learning process, and the grades obtained by the learners have improved since the implementation of blended learning, indicating that a combination of traditional teaching and online techniques is useful to the learners (Ahmed, 2011;Al-Hasan, 2013;Almasaeid, 2014;Chen and Jones, 2007;Dowling, Godfrey and Gyles, 2003;Khader, 2016;Kagohara, et al, 2010;Lança and Bjerre, 2018;McLaughlin, et al, 2015;Qutieshat, Abusamak and Maragha, 2019).…”
Section: Previous Studiesmentioning
confidence: 99%